Evaluating households’ community participation: Does community trust play any role in sustainable development? - Hu, Guangyin; Wang, Jing; Laila, Ume; Fahad, Shah; Li, Jinjie (Frontiers in Environmental Science, 2022)
Traditional community support, prevention from disasters, and mitigation depend on the top-down mode of management regulated by the government. This study aims to analyze the association between social networks and its structure on the decision of households’ participation in community. A households survey was conducted in Yangling district of Shaanxi province of China and 393 households were targeted. An ordered multi classification logistic regression model was utilized to empirically analyze the association between the variables. The results showed that social networks have a significant positive impact on the households’ participation in cooperatives/communities. Among other variables, network interaction, network learning, network trust, and households’ participation in green energy technologies and cooperatives/community showed significant and positive correlation, but the variable network reciprocity was found to be negatively correlated to the adoption of green energy technologies. Study findings further revealed that, there is an interaction effect in the participation of households’ behavioral decision-making and joining cooperatives. Furthermore, the social experience of the head of the household and the source of income of the family showed a significant positive association with households’ participation in cooperatives/communities. Based on the study findings, it is suggested that the utilization and cultivation of households’ social network, service level of cooperatives need to be improved.